Construction and validation of an instrument for the structural assessment of wards for urinary continence in older adults - Roberta Pereira Góes; Larissa Chaves Pedreira; Camila Oliveira Valente; Fernanda Carneiro Mussi; Monaliza Lemos de Souza; Juliana Bezerra do Amaral (Universidade de São Paulo, 2020)
Objective: to build and validate an instrument for structural assessment of wards for the preservation of urinary continence in hospitalized older adults. Method: this is a methodological study divided into two stages. The first corresponded to an integrative literature review that guided the construction of the instrument. The second consisted of the content validation stage of the instrument, by means of expert consensus, using the Delphi technique. The selected experts were recognized in the field and authors of the articles included in the integrative review. Results: six experts participated in the content validation, which resulted in the "Instrument for Structural Assessment of Wards for the Preservation of Urinary Continence in Older Adults", composed of 27 items, distributed in three dimensions: "physical structure", "human resources", and "material resources". Two Delphi rounds were carried out for validation, resulting in a final version with 83% agreement among the experts. Conclusion: the instrument reached content validity, requiring application for clinical validation. However, it can be used by researchers and health staff in hospital settings, in order to identify structural weaknesses and guide the priority of interventions for the quality and safety of this care.